Barriers to birth preparedness and complication readiness among pregnant women in rural Ethiopia: using a mixed study design, 2020 - Abdi Geda Gedefa; Alazar Ayalew Bekele; Keno Melkamu Kitila; Lemi Bacha Eba (BMJ Open)
Objective To assess birth preparedness and complication readiness (BPCR) and associated factors among pregnant women in Bachoo District, Oromia, Ethiopia.Design A mixed cross-sectional study design was employed to conduct this study.Setting A community-based cross-sectional study was done in the rural community of Bachoo District of Iluu Abbaa Boor Zone, Oromia Region, Southwest Ethiopia.Participants A total of 307 pregnant women participated in the quantitative study, 51 respondents were involved in the qualitative part. A simple random sampling technique was used to select the final respondents. Data were entered into EpiData V.3.1 and analysed using SPSS V.22. Binary and multivariable logistic regression analysis was done. The level of statistical significance was declared at a p<0.05. Three focus group discussions and 21 in-depth interviews were conducted, and the data were analysed using thematic analysis and triangulated to support the findings of the quantitative study.Result The prevalence of BPCR was 30.6%. Being governmental employee ((adjusted OR, AOR=3.22 95% CI (1.49 to 11.79)), educational status of secondary and above ((AOR=1.9 95% CI (1.15 to 3.84)), multigravidity ((AOR=5.96, 95% CI (1.18 to 3.68)), having four or above ANC visits ((AOR=4.25 CI (1.38 to 7.84)), participating in pregnant women conference ((AOR=2.11 95% CI (1.07 to 3.78)), having good knowledgeable of obstetrics danger signs ((AOR=10.4 95% CI (5.57 to 19.60)), hearing the term BPCR ((AOR=4.36, 95% CI (1.93 to 9.82)) were among factors significantly associated with BPCR. The qualitative study also showed that poor maternal knowledge on birth preparedness and obstetric danger signs, negligence and weak support systems in the community were among the main barriers.Conclusion and recommendation This study demonstrated that the practice of BPCR in the study area was very low. Therefore, healthcare providers in the study area should strengthen BPCR knowledge through educating women the community at large.